Identificação e genótipos de giardia intestinalis em humanos e animais no noroeste do estado de São Paulo, Brasil - Godoy, Elenir Alves Macedo de (2012)
Introduction: Giardia duodenalis is the protozoan frequently found in the intestinal infection causing gastroenteritis worldwide. The G. duodenalis is complex specie with at least seven different assemblages. The A and B assemblages have been associated with infections in human as well as in other mammals, while the other assemblages have demonstrated to prefer different animal species. Genotypes C and D was include isolated of dogs; E is related to production animals, such as, goats, pigs, sheeps and bovines and genotypes F and G are exclusive of domestic felines and rats, respectively. Molecular studies had also disclosed that the genotype presents two sub-groups; A-I and A-II and B; BIII and BIV. Objective: The present study objectified to study domestic, the epidemiology of the G. intestinalis genotypes in human beings, canines, domestic felines, ovines, bovines and caprines, specifically in relation to the standards of transmission in the Northwestern region of the São Paulo State, Brazil, and to evaluate the hypothesis of zoonotic infection. Methods: During the period of July 2009 to October 2010 they had been studied fecal samples of 61 animals and 154 human beings proceeding from the city of Araçatuba, State of São Paulo. The feaces samples of the animals had been gotten in the Control center of Zoonoses of the city and in the Veterinarian Hospital of Universidade Estadual Paulista Julio de Mesquita Filho . The human fecals specimens had been collected in day-care centers in the periphery of the city and laboratories of Clinical Analysis of the private net of the city. The parasitologic diagnosis was made by optic microscopy, by the techniques of Faust and Hoffmann, Pons & Janer. The genotypes of G. intestinalis had been characterized by PCR-RFLP and confirmed by sequencing analysis of the ß-giardin gene. Results: The human beings samples had shown a positivity of 25.3% (39/154), of these, the percentage in children was of 26.8% (36/134), and in adults got 15% of positive samples (3/20). The frequency of G. intestinalis between the studied animals was of 23% (14/61). A total of 32 isolated of G. intestinalis obtained from human beings feces and 6 of the dogs and cats had been characteristic only of the genotype A (AI and AII/AIII). Conclusions: Regarding the Giardíase frequency, our results are similar to the majority of described percentages in children and adults from São Paulo State and other States of Brazil. The prevalence observed in the animal population is in accordance with the described worldwide. The present study was made possible the detention of the considered genotypes zoonotics of G. intestinalis, circulating between the domestic and human animals of the city of Araçatuba, inferring the possibility of zoonotic transmission of the parasite in the northwest region of the State of São Paulo. The absence of these genotypes in production animals offers the perspective that those are not involved in the chain of transmission to the man in the same locality.